Answer:
y = -5x + 1
Step-by-step explanation:
y - 6 = -5 (x + 1)
distribute -5 (x + 1) by multiplying
y - 6 = -5x - 5
than add 6 to both sides
y = -5x + 1
Answer:
Step-by-step explanation:
Part A - Where did Phillip make a mistake? Justify your answer using complete sentences.
Use order of operation (PEMDAS)
He should multiply 8 x 4 first
Part B - Solve the expression correctly in the space below.
(5 x 9) - 8 x 4
= 45 - 32
= 13
Part C - Use the same rules of order of operations to solve the expression (8-4) +9 x 3. Explain your steps as you solve it.
(8-4) + 9 x 3
Step 1: 4 + 9 x 3 (Subtract in the parenthesis first)
Step 2: 4 + 27 (Multiply 9 x 3)
Step 3: 31 (Add)
Given:
In the given ΔXYZ,
Base = 22
Height = 23.1
Also,
Base = 31.9
Height = 15.9
To find the area of the given ΔXYZ.
Formula
The area of a triangle is
![A = \frac{1}{2} bh](https://tex.z-dn.net/?f=A%20%3D%20%5Cfrac%7B1%7D%7B2%7D%20bh)
where, b be the base and
h be the height.
Now,
Taking, b = 22 and h = 23.1 we get,
sq unit
Again,
Taking,
b = 31.9 and h = 15.9 we get,
sq unit
Therefore,
We can find the approximate area of the triangle by following two expression
a)
and
b) ![\frac{1}{2} (31.9)(15.9)](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D%20%2831.9%29%2815.9%29)
Answer:
6
Step-by-step explanation:
A conjunction is a word that joins words or phrases. <em>For, and, nor, but, or, yet, so...</em>The conjunction in this sentence would be and.
(<em>most</em> is an adverb, <em>wow</em> is an interjection, and <em>of</em> is a preposition)